2012
DOI: 10.1073/pnas.1203870109
|View full text |Cite
|
Sign up to set email alerts
|

Dependence on nuclear factor of activated T-cells (NFAT) levels discriminates conventional T cells from Foxp3 + regulatory T cells

Abstract: Several lines of evidence suggest nuclear factor of activated T-cells (NFAT) to control regulatory T cells: thymus-derived naturally occurring regulatory T cells (nTreg) depend on calcium signals, the Foxp3 gene harbors several NFAT binding sites, and the Foxp3 (Fork head box P3) protein interacts with NFAT. Therefore, we investigated the impact of NFAT on Foxp3 expression. Indeed, the generation of peripherally induced Treg (iTreg) by TGF-β was highly dependent on NFAT expression because the ability of CD4 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
147
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 120 publications
(168 citation statements)
references
References 52 publications
12
147
4
Order By: Relevance
“…This is in line with recent studies showing that members of the Ca 2+ -dependent NFAT transcription factor family regulate FOXP3 expression in iTregs (68,69). NFAT binds, together with SMAD2/3, directly to the conserved noncoding sequence 1 in the Foxp3 locus and regulates FOXP3 expression in response to TCR stimulation and TGF-β (68)(69)(70). In addition to Foxp3, expression of other genes associated with iTregs was significantly deregulated in STIM1-deficient T cells.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This is in line with recent studies showing that members of the Ca 2+ -dependent NFAT transcription factor family regulate FOXP3 expression in iTregs (68,69). NFAT binds, together with SMAD2/3, directly to the conserved noncoding sequence 1 in the Foxp3 locus and regulates FOXP3 expression in response to TCR stimulation and TGF-β (68)(69)(70). In addition to Foxp3, expression of other genes associated with iTregs was significantly deregulated in STIM1-deficient T cells.…”
Section: Discussionsupporting
confidence: 76%
“…Similar observations were made in NFAT2-deficient CD4 + T cells, which fail to efficiently differentiate into FOXP3 + iTregs, while the remaining iTregs were functional (68). Together, our data indicate that STIM1-mediated Ca 2+ signaling is essential for the conversion of naive CD4 + T cells into iTregs, but that it is largely dispensable for their stability and suppressive functions.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Second, analysis of NFAT translocation demonstrated that, compared with Teffs, Tregs displayed an increased nuclear localization of NFAT in the presence of tacrolimus. These data differ from two previous publications reporting reduced effects of CNIs on Tregs (28,29). Vaeth et al (29) failed to detect NFAT in the nucleus of Tregs and concluded that their function …”
Section: Foxp3contrasting
confidence: 56%
“…In particular, it has been demonstrated that the generation of peripherally induced Tregs by TGF-b is highly dependent on NFAT expression (48). NFAT proteins interact with Fos-Jun (AP-1) transcription factors to form cooperative NFAT/AP-1 complexes that are critical for the induction of cytokine genes and other activation-associated genes.…”
Section: Discussionmentioning
confidence: 99%